0014 Genome-wide Association Analysis Of Excessive Daytime Sleepiness In The Uk Biobank Identifies 42 Novel Loci. (27th April 2018) - Wang, H; Lane, J M; Dashti, H S; Jones, S; Cade, B E; Song, Y; Patel, K; Frayling, T M; Weedon, M N; Lawlor, D A; Rutter, M K; Redline, S; et al.
Abstract: Introduction: Excessive daytime sleepiness (EDS) is a heritable trait affecting 10–20% of the population. EDS can occur as a consequence of insufficient sleep, poor sleep quality, or as a manifestation of a sleep disorder. EDS is associated with higher risk for motor accidents, and is linked to cognitive impairment. We aimed to explore individual vulnerability to EDS by identifying genetic variants and molecular pathways underlying EDS and define shared biological mechanisms and causal links with other diseases. Methods: We performed a genome-wide association analysis of self-reported EDS using 452, 071 individuals of European ancestry in the UK Biobank. Linear mixed regression model was applied adjusting for age, sex, population structure and technical covariates. Follow-up analyses of genes, tissue, pathway and ontology enrichment, partitioned heritability, and pair-wise genetic correlations to GWAS for 233 traits were performed. We tested if a genetic risk score (GRS) of previously reported genetic variants for specific sleep disorders associated with EDS. Secondary analyses adjusted for BMI and stratified by sex. Results: We identified 42 significant novel loci (p<5x10 -8 ) and 2 additional sex-specific loci associated with EDS, with enrichment of genes expressed in brain tissues and central nervous pathway. Genes previously reported associated with sleep and metabolic traits and novel genes were identified, including INADL, LMOD1, SNX17, CADM2, ECE2, GABRA2, SLC39A8, POM121L2, ASAP1, CACNA1C, KSR2, CPEB1, PRKCB, RAI1 and NKAIN2 . Strong genetic correlations were observed between EDS and BMI, coronary artery disease and psychiatric diseases (P<10 –4 ), suggesting shared underlying biological mechanisms. The GRS for restless leg syndrome and narcolepsy were significantly associated with EDS (P=2x10 -4 and 1x10 -2 respectively), indicating genetic overlap with EDS. Conclusion: This largest GWAS for EDS identifies multiple novel genetic loci that can offer biological insights into pathways that contribute to EDS and consequential sleep disorders. Support (If Any): This work is supported by grants NIH R01 HL113338, NIH R35 HL135818, NIH F32DK102323, NIH 4T32HL007901, NIH R01DK107859, the Wellcome Investigator Award, and the University of Manchester Research Infrastructure Fund - MRC (MC_UU_12013/5)